An annotation on Batu Acheh Islamic gravestones in Pulau Pinang, Malaysia - Muhammad Nabil Ahmad Nadri
This study was conducted in order to annotate different relevant data on the subject of classical Malay-Muslim Islamic gravestones known as Batu Aceh in the state of Pulau Pinang, Malaysia. Batu Aceh are valuable lithic (stone) archaeo-historical artefacts that provide various information on the complex local society in the past. Previously, the construction of the Malay World’s historical narrative, especially pertaining the presence and emergence of the earliest Islamic society in the region, began with the study over different stone inscriptions, such as those in Permatang Pasir (Pahang), Leran (Java), Pangrang (Vietnam) and Kuala Berang (Terengganu). Likewise, Batu Aceh's role is similar as a form of primary source where they are mainly observed from their patterns of distribution, physical aspects as well as historical documentation in explaining their presence. Batu Aceh are civilisational material and philosophical products of the local society of the past; they were manufactured by professional artisans from as early as 15th century CE to 19th century CE, when they began to transform into modern gravestone manufacture. Batu Aceh in Pulau Pinang are studied via extensive annotation of data based on three main aspects, which are: the sites and distribution, the forms and features, and the historical context. The first aspect demonstrates that Batu Aceh gravestones do exist in significant numbers at different historical sites and they are a part of a larger similar Islamic gravestone culture found across the region. The second aspect annotates the physical manifestation of the artefacts, namely through dimension (size), typology, ornamentation and epigraphy (inscription) as they provide information over the identity of the deceased and the society which once revolved around their presence vis-a-vis status, gender, name, date, etc. The final annotation provides historical context of Batu Aceh from various different sources, such as old manuscripts and traditions, colonial documents and modern academic works. This aspect also helps establish the early presence of Malay Muslims as developers and rulers of the state from 15th century CE until early modern time. The findings of this study will help in strengthening the existence of Malay-Muslim society in Pulau Pinang, especially against the colonial and Eurocentric historical narratives.